Pemberdayaan Masyarakat Melalui Pemanfaatan Sumber Daya Alam Lokal untuk Ecoprint - Edison, Firnandito; Sari, Liana Permata; Putri, Gesika Gemintang; Primadani, Ericha Tyas; Widowati, Karina Putri; El Falah, Muhammad Miftah; Perdana, Maulivia Trisma; Herlambang, Akbar Adji; Putra, Mahendrata Adwitya; Muttaqin, Moh. Zaenal; Kesetyaningsih, Tri Wulandari (Universitas Muhammadiyah Yogyakarta, 2025)
The ecoprint batik training program was implemented as part of the Community Service Program in Potro Hamlet, Purwobinangun Village, Pakem District, Sleman Regency, D.I Yogyakarta on January 24th - February 23rd 2025. This program is a flagship program of Community Service activities UMY. This program aims to improve the skills and creativity of the community, especially PKK mothers, in creating craft products with economic value through the utilization of local natural resources. This training is expected to introduce the potential of Potro Hamlet as an ecoprint center, increase community interest in ecoprint activities, and optimize its use as a source of additional income. The training methods include socialization, preparation of natural materials (leaves with pigments and tannins), introduction to basic pounding techniques, direct practice, and evaluation. The pounding technique was chosen because of its simplicity, allowing participants to directly practice making ecoprint motifs by hitting leaves on cloth. Success is measured by participant enthusiasm, understanding of techniques, and ability to implement ecoprint techniques. The results showed a significant increase in participants' skills in making ecoprint batik. The PKK mothers showed high enthusiasm in participating in the training, successfully understood the basic pounding technique, and were able to produce simple yet aesthetic ecoprint products. The discussion showed that the ecoprint training succeeded in improving community skills, opening up new economic potential through the utilization of local natural resources, and supporting the development of environmentally friendly fashion products. This activity also fostered a sense of love for the environment and increased awareness of the importance of using environmentally friendly materials in everyday life. The ecoprint training had a positive impact on improving the skills and economic potential of the Potro Hamlet community. The implications of the results indicate the need for the continuation of similar training programs, accompanied by marketing assistance and product development to maximize the potential of ecoprint as a source of additional income and local identity